Answer:
C
Step-by-step explanation:
ley y = f(x) and rearrange making x the subject
y =
- 1 ( add 1 to both sides )
y + 1 =
( multiply both sides by (x + 5)
(y + 1)(x + 5) = 1 ← expand factors using FOIL
xy + 5y + x + 5 = 1 , that is
xy + x + 5y + 5 = 1 ( factor first/second and third/fourth terms on left side )
x(y + 1) + 5(y + 1) = 1 ← factor out (y + 1) from each term on left side
(y + 1)(x + 5) = 1 ( divide both sides by (y + 1) )
x + 5 =
( subtract 5 from both sides )
x =
- 5
Change y back into terms of x with x =
(x) , then
(x) =
- 5 where x ≠ - 1